Travelling ionospheric disturbances over Kharkiv, Ukraine, accompanying the operation of EISCAT heater facility - Panasenko, S. V.; Rietveld, M. T.; La Hoz, C.; Domnin, I. F. (НТУ "ХПІ", 2014)
We have detected the travelling ionospheric disturbances (TIDs) over Kharkiv with periods of 40–80 min occurring in the time range between 09:00 and 10:30 UT on November 22 and between 10:00 and 12:00 UT on November 23, 2012 during and after the operation of the EISCAT heater facility. The duration of these disturbances were less than 120–180 min. The relative amplitudes of the TIDs in electron density ranged from 0.05 to 0.15 and those in electron and ion temperatures were about 0.02 – 0.05. Assuming that these TIDs have been generated in the heated region, we described the possible mechanisms of their generation.

Виявлено рухомі іоносферні збурення (РІЗ) над Харковом з періодами 40–80 хв., що мали місце впродовж 09:00 – 10:30 UT 22 листопада та з 10:00 до 12:00 UT 23 листопада 2012 р. в період і після роботи нагрівного стенда EISCAT. Тривалість цих збурень не перевищувала 120–180 хв. Відносні амплітуди РІЗ концентрації електронів складали 0.05 – 0.15, а РІЗ температур електронів та іонів дорівнювали 0.02 – 0.05. За припущення, що ці РІЗ були згенерровані в нагрітій області, описано можливі механізми їх генерації.
Keywords: travelling ionospheric disturbances; powerful HF radio waves; incoherent scatter radar; heater facility; рухомі іоносферні збурення; потужні радіохвилі; радіохвилі; радар некогерентного розсіяння; нагрівний стенд